Understanding phase stability of Al-Co-Cr-Fe-Ni high entropy alloys. (5th November 2016) - Zhang, Chuan; Zhang, Fan; Diao, Haoyan; Gao, Michael C.; Tang, Zhi; Poplawsky, Jonathan D.; Liaw, Peter K.
Abstract: The concept of high entropy alloy (HEA) opens a vast unexplored composition range for alloy design. As a well-studied system, Al-Co-Cr-Fe-Ni has attracted tremendous amount of attention to develop new-generation low-density structural materials for automobile and aerospace applications. In spite of intensive investigations in the past few years, the phase stability within this HEA system is still poorly understood and needs to be clarified, which poses obstacles to the discovery of promising Al-Co-Cr-Fe-Ni HEAs. In the present work, the CALPHAD approach is employed to understand the phase stability and explore the phase transformation within the Al-Co-Cr-Fe-Ni system. The phase-stability mapping coupled with density contours is then constructed within the composition - temperature space, which provides useful guidelines for the design of low-density Al-Co-Cr-Fe-Ni HEAs with desirable properties. Graphical abstract: Highlights: Clarify the bcc-based structure (Bcc_A2 and/or Bcc_B2) using the APT Elucidate the alloying element effect on the stability of the single Fcc_A1 solid solution HEA Understand the density evolution versus concentration and temperature